Factors influencing the adoption of social networking sites: Malaysian Muslim users perspective - Jan, Muhammad Tahir; Abdullah, Kalthom; Momen, Abdul (2013)
For social, emotional and cognitive development of the human being, Social Networking Sites (SNSs) provide an important milieu that eventually leads the human experience to the new era. Malaysia is one of the top countries where social networking sites are adopted faster. The purpose of this study is to determine the factors influencing the Malaysian Muslim users to adopt social networking sites. It will justify the social, educational, technological and other factors behind the adoption of social networking sites like Facebook, twitter and MySpace. The paper is conceptual in nature and proposes that a future research can be conducted with the Structural Equation modeling approach to sort out the significance and the relative importance of these factors behind the Muslim users’ adoption of social networking sites in Malaysia.